Spexin Acts as Novel Regulator for Bile Acid Synthesis - Lin, Cheng-yuan; Zhao, Ling; Huang, Tao; Lu, Lin; Khan, Mahjabin; Liu, Jie; Zhong, Linda L. D.; Cai, Zong-wei; Fan, Bao-min; Wong, Anderson O. L.; Bian, Zhao-xiang (Frontiers in Physiology, 2018)
Spexin is a novel hormone involved in obesity and diabetes while its biofunctional significance in lipid metabolism is still to be comprehended. Global metabolomic analysis in the present study revealed multiple metabolic pathways altered by spexin intraperitoneal (i.p.) injection in rat serum, which are highlighted by the changes in several bile acid metabolites. In rats, spexin (300 μg/kg) could dramatically reduce hepatic and circulating total bile acids (TBA) level compared with the controls. Correspondingly, treatment with spexin by i.p. injection for 28 days led to significant decrease in serum TBA and gallbladder weight in C57BL/6J mice. In enterohepatic circulation system, spexin effectively reduced TBA levels in mouse liver and gallbladder but not the intestine. Hepatic cholesterol 7α-hydroxylase 1 (CYP7A1) expression, unsurprisingly, was suppressed by spexin injection. Both GALR2 and GALR3 antagonists reversed the inhibitory effects of spexin on concentrations of serum TBA and 7 α-hydroxy-4-cholesten-3-one (C4), and hepatic CYP7A1 expression. Finally, negative correlations were observed between serum spexin and total cholesterol (TC), total bile acid (TBA), tauro-chenodeoxycholate (TCDCA), as well as glycochenodeoxycholate (GCDCA) in 91 healthy volunteers. These findings illuminate the intrinsic importance of spexin in the regulation of bile acid synthesis and metabolism.